2020
DOI: 10.1080/20550340.2020.1826772
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of in-situ AFP process parameters using CF/LM-PAEK

Abstract: In recent years the use of thermoplastics has become popular in aerospace applications, with a primary focus on fiber-reinforced composites. Displaying greatly improved mechanical properties, new components using these materials still need to be characterized and their suitability for aviation applications demonstrated. A common restriction to the implementation of fiber-reinforced thermoplastic parts is the almost default autoclave manufacturing, which is both time consuming and expensive. Aiming for a more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 3 publications
(4 reference statements)
1
21
0
Order By: Relevance
“…Though this will be discussed in more details in the last part of this review, a current limit is linked to the high speed of the roller (Fig. 4) causing fast cooling rates and thus low degrees of crystallinity [15,18,58,59,61]. For example, the crystallinity reached for "in-situ" consolidated CF/PAEK through AFP is around 10% as reported in [61] and 18% for CF/PEEK in the study of Comer et al [55], far below the ones obtained for autoclave processed pieces (see Table 1).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Though this will be discussed in more details in the last part of this review, a current limit is linked to the high speed of the roller (Fig. 4) causing fast cooling rates and thus low degrees of crystallinity [15,18,58,59,61]. For example, the crystallinity reached for "in-situ" consolidated CF/PAEK through AFP is around 10% as reported in [61] and 18% for CF/PEEK in the study of Comer et al [55], far below the ones obtained for autoclave processed pieces (see Table 1).…”
Section: Tablementioning
confidence: 99%
“…A second consequence of this short processing time is the fact that it will lead to low degrees of crystallinity, hence lower mechanical properties for the composite. To solve this, Schiel et al [61] propose to anneal afterwards the obtained laminate at a temperature above T g . Alternatively, increasing the tool temperature leads to lower cooling rates and higher degree of crystallinity as well.…”
Section: Optimization Of the Consolidation Processmentioning
confidence: 99%
“…The deconsolidation phenomenon is well known in TPC processing, such as automated tape placement [3] or TPC thermal stamping. In these cases, mainly homogenous deconsolidation is investigated.…”
Section: Deconsolidation Of the Laminat Deconsolidation Of The Laminate Ementioning
confidence: 99%
“…Crystallisation development, not only in terms of the degree of crystallisation but also in terms of the morphology, is a key consideration in in-situ consolidation. A recent study using novel materials (low melting poly-aryl-ether-ketone (PAEK)) demonstrated that several variations can be obtained in terms of the crystallinity and single lap shear by modifying the lamination speed, nip point temperature, and tooling temperature, and by performing post-manufacturing tempering [ 12 ].…”
Section: Introductionmentioning
confidence: 99%